# Simplify. 6y+3+ 3x^2 - y^2 – 5x + 2x^2 + 3x + 2y

2 months ago

## Solution 1

Guest #5492590
2 months ago

The required simplified value of the given expression is given as 5x² - y² -2x + 8y + 3.

### What is simplification?

The process in mathematics to operate and interpret the function to make the function or expression simple or more understandable is called simplifying and the process is called simplification.

here,
Given expression,
= 6y+3+ 3x² - y² – 5x + 2x² + 3x + 2y

= 5x² - y² -2x + 8y + 3

Thus, the required simplified value of the given expression is given as 5x² - y² -2x + 8y + 3.

brainly.com/question/12501526

#SPJ5

## Solution 2

Guest #5492591
2 months ago

Step-by-step explanation:

Combine like terms

8y + 3 + 5 + 2x -

## 📚 Related Questions

Question
According to the Fundamental Theorem of Algebra, how many roots exist for the polynomial function?
Solution 1

5

Step-by-step explanation:

Question
Carrie filled her watering can with 5 liters of water. When she finished watering her plants, there was still 1,500 milliliters of water in her can. How much water did she use? Circle ALL that apply.
Solution 1

Step-by-step explanation:

Question
Briella deposited \$3,750 into her checking account. She earns 3.5% interest rate. How much interest will Briella earn after 3 years?
Solution 1

393.75

Step-by-step explanation:

Question
Question 4/3 y=1 what is y?​
Solution 1

y=  3/4

Step-by-step explanation:

Solution 2

y=3/4

Step-by-step explanation:

4/3y=1

divide both sides by 4/3

1 divided by 4/3 is 3/4 so:

y=3/4

Question
PLZ HELP x + y - 6 =0 x - y = 0 what is the solution of the system? (-3,3) (3,-3) (3,3)
Solution 1

(3, 3)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

1. Brackets
2. Parenthesis
3. Exponents
4. Multiplication
5. Division
7. Subtraction
• Left to Right

Equality Properties

• Multiplication Property of Equality
• Division Property of Equality
• Subtract Property of Equality

Step-by-step explanation:

Step 1: Define Systems

x + y - 6 = 0

x - y = 0

Step 2: Rewrite Systems

x + y - 6 = 0

1. Add 6 on both sides:                    x + y = 6

Step 3: Redefine Systems

x + y = 6

x - y = 0

Step 4: Solve for x

Elimination

1. Combine 2 equations:                     2x = 6
2. Divide 2 on both sides:                    x = 3

Step 5: Solve for y

1. Define equation:                     x - y = 0
2. Substitute in x:                        3 - y = 0
3. Subtract 3 on both sides:       -y = -3
4. Divide -1 on both sides:          y = 3
Question
Raphael paid \$644 for a camera during a 20% off sale. What was the​ camera's regular​ price?
Solution 1
644 is 80% of the regular price, so price=644/0.8 = 805 \$
Solution 2
\$S = \$P - \$P × 0.15 = \$P(1 - 0.2) = \$P × 0.8. Do a litte algebra, you get \$S=.8\$P.
\$S stands for sale price, \$P stands for original price. We know the sales price: \$644. We know now that 644=.8\$P. Divide both sides by .8 and you get \$P=\$805. Hope this helps!
Question
PLZ HELP In which of the following intervals does the trigonometric inequality sec(x)
Solution 1

(cot)x always hold

Step-by-step explanation:

Question
7/8 times 3/5 plz help !!
Solution 1

21/40

Step-by-step explanation:

Question
landscape designer has 4/5 ton of mulch to divide equally among 8 customers. how much mulch will each customer get?
Solution 1

1/10

Step-by-step explanation:

4/5x1/8=4/40=1/10

Question
• Simplify the expression. 47(-20)(-5) = ?
Solution 1
Let’s break this down :)

47 * -20 = -940
-940 * -5 = 4,700

2647929
842281
748681
586256
406852
368373
348603
324927
199835
130075
112100
106146
77164
23213
22589
19607
17108
13966
10987
3389